Emerging Adults’ Experiences of Dating Violence: A Qualitative Exploration - Víllora, Beatriz (Victims & offenders, 2025)
Dating violence is a significant issue among emerging adults. Using Bronfenbrenner’s ecological model, this study investigates its precursors through interviews with 21 individuals aged 18–25 who experienced dating abuse. By applying the social-ecological model, this study underscores the complexity of dating violence, highlighting the necessity of addressing it through a multifaceted approach. Four main themes emerged: personal experiences of dating violence, precursors to violence, technology’s impact, and coping strategies. Psychological violence, particularly controlling behavior, being most common. Findings highlight the importance of individual and relational factors, social networks, and media influence. Overall, a comprehensive approach integrating social support, professional intervention, and societal changes seem to be essential.